Lowering Blood Pressure After Following Slow Deep Breathing Therapy In Elderly Group - Teti Noermaya Rifadillah; Ricky Riyanto Iksan; Sri Atun Wahyuningsih (Comprehensive Health Care, 2021)
Hypertension in the elderly is a non-communicable disease that is one of the main causes of premature death in the world which results in complications in the elderly due to physical changes. This study aims to identify lowering blood pressure in the elderly with hypertension. This research method uses a case study design and consists of four respondents. Data collection was carried out in the Duri Kepa Community Health Center Village, Kebon Jeruk District, West Jakarta on 26-29 May 2021. The results of the research carried out were a significant decrease on the 3rd and 4th days from Stage II (moderate) to Stage I (mild). ) and from Stage III (severe) to Stage II (moderate). Conclusions from this research ApplicationSlow Deep Breathing therapy reduces blood pressure significantly, as evidenced by data on the characteristics of elderly people with hypertension.